2022
DOI: 10.1039/d2tc03031d
|View full text |Cite
|
Sign up to set email alerts
|

Reversible thermochromism, temperature-dependent conductivity and high stability for a laminated bismuth(iii)–silver(i) hybrid double perovskite

Abstract: Lead free hybrid perovskite materials have attracted tremendous consideration due to their applications in photovoltaic, optoelectronics and thermal sensors etc. Herein, we isolated a new stable semiconductive 2D bismuth(III)-silver(I) iodide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…4b), which is in accordance with the color of dark-red and narrower than those of many high-performance light absorbers (Fig. 4c 16,20,[23][24][25]30,39,[46][47][48][49][50] Mott-Schottky plots were used to further study the optical behavior of the title compound. As shown in Fig.…”
Section: Optical Propertiessupporting
confidence: 53%
See 3 more Smart Citations
“…4b), which is in accordance with the color of dark-red and narrower than those of many high-performance light absorbers (Fig. 4c 16,20,[23][24][25]30,39,[46][47][48][49][50] Mott-Schottky plots were used to further study the optical behavior of the title compound. As shown in Fig.…”
Section: Optical Propertiessupporting
confidence: 53%
“…Representative examples include [La(DMSO) 8 ]Bi 2 I 9 (2.21 eV), [Bi(DMSO) 8 ]Bi 2 I 9 (2.17 eV), [AmV]BiI 5 (1.54 eV), [PiC 2 ] 2 Bi 2 I 10 (2.08 eV), PiC 5 BiI 5 (1.73 eV), [PiC 5 ] 2 Bi 4 I 16 (2.10 eV), [HpipeH 2 ] 2 Bi 2 I 10 ·2H 2 O (1.80 eV), LiBiI 4 ·5H 2 O (1.70 eV), KBiI 4 ·H 2 O (1.76 eV), [CH 3 NH 3 ] 3 Bi 2 Br 9 (2.50 eV), [H 2 MPP] 2 AgBiI 8 (2.26 eV), [APP] 4 AgBiI 8 ·H 2 O (2.12 eV), [AMP] 4 AgBiI 8 ·H 2 O (2.07 eV), [Ni(bipy) 3 ]AgBiBr 6 (2.06 eV), [NH 4 ] 3 Bi 2 I 9 (2.04 eV), [C 8 H 20 N] 2 Ag 2 Bi 4 I 16 (1.93 eV) and [Et 4 N] 2 Cu 2 Bi 2 I 10 (1.89 eV). 16,20,23–25,30,39,46–50…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 There have been many reports on Bi-based iodide double perovskites whether inorganic or organic-inorganic hybrid compounds. [36][37][38] Sb 3+ , similar to Bi 3+ , is also explored as a candidate to replace Pb 2+ in lead-free metal halide perovskites. Xia et al prepared a double perovskite of Cs 2 AgSbCl 6 , which is found to have a varied band gap associated with different body colors.…”
Section: Introductionmentioning
confidence: 99%